Pengaruh Model Pembelajaran Kooperatif Think Pair and Share terhadap Kemampuan Komunikasi Matematis - Devi Anisa Sibuea (Sepren, 2020)
This study aims to determine whether there is an effect of the Think Pair and Share Cooperative learning model on mathematical communication skills in the material of Cartesian Coordinates for Class VIII of the Private Junior High School in Silangkitang Development. This study used a quasi-experimental method with the study population, namely all students of class VIII private junior high school construction of silangkitang. With purposive sampling technique and the sample in this study is class VIII-2. The instrument used is the Post-test from the learning outcomes that have been tested for the validity of the instrument and the observation sheet of communication skills. From the calculation results obtained the regression equation is 1 = -122.33 + 2.47X. For the posttest regression linearity test, it is obtained that F_count = 4.12, then F table> F_count or 4.12> 1.2827, then Ha is accepted. So that there is a linear relationship between the think pair and share cooperative learning model on students' mathematical communication skills. Then to test the meaning of the regression between X and Y obtained F_count = 7.9430 then F table <F_hitung or 1.81 <7.9430 then Ha accepted. So that there is a meaningful relationship between think pair and share cooperative learning with mathematical communication skills. Based on the results of the analysis of the linearity test and the significance of the regression test, it can be concluded that there is an influence between the think pair and share cooperative learning model on the mathematical communication ability of the Cartesian coordinate material for Class VIII of the Silangkitang Development Private Middle School. So it is hoped that this learning model can be used as an alternative to improve students' mathematical communication skills.